ONTOGENETIC FEATURES OF PHYSICAL FITNESS AND FUNCTIONING OF THE CENTRAL NERVOUS SYSTEM OF COLLEGE STUDENTS - Milashechkin, V.S.; Dzhandarova , T.I.; Gernet , I.N.; Rusanov, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify ontogenetic tendencies of physical readiness and psychophysiological parameters of the central nervous system in the process of teaching female students in college. Methods and structure of the study. In the course of the work, the following were determined: the time of a simple reaction to light and sound, a complex reaction to light, that is, a choice reaction and a reaction to a moving object in groups of college students aged 16-20. Physical tests were used to assess physical fitness. Results and conclusions. The maximum increase in the time of the sensorimotor reaction at the age of 17 was revealed in girls during college education, which indicates the depletion of the adaptive capabilities of the CNS. At the age of 18, the parameters of the sensorimotor reaction to light and sound stabilize, and by the age of 20, there is some gradual decrease. By the end of training, there is a decrease in physical fitness indicators, which can adversely affect the state of health and motor functions of the body. According to preliminary data, physical fitness and psychophysiological parameters of the functioning of the central nervous system have different age dynamics during the training of college students.